Towards an actionable One Health approach - Xiao-Xi Zhang; Lederman, Z.; Le-Fei Han; Schurer, J.M.; Li-Hua Xiao; Zhi-Bing Zhang; Qiu-Lan Chen; Pfeiffer, D.; Ward, M.P.; Sripa, B.; Gabriël, S.; Dhama, K.; et al. (Springer, 2024)
Background